Perceiving sustainability and practicing community based rehabilitation : a critical examination of the Western Cape Rehabilitation Centre (WCRC) as a case study - Mukanya, Ronald (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.